Manajemen Reputasi Digital PT. KAI Pasca Kecelakaan di Bekasi Timur - Dafina Dewi Puspasari; Adelia Dwi Ratri; Farhatuz Zahra; Dyah Ayu Prazna Paramitha; Agung Dharmajaya (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
The development of digital media has made an organization's reputation as a strategic asset greatly influenced by public perception in the digital space. In the transportation industry, everything related to safety has the potential to trigger a reputation crisis that can reduce the level of public trust. This study aims to analyze the digital reputation management of PT. KAI after the accident at East Bekasi Station using SCCT and Online Reputation Management (ORM) theory. This research uses descriptive qualitative approach with Case Study Method. Data collected through observation of digital communication PT. KAI on social media and public response that emerged after the incident. The results showed that the incident is included in the accidental cluster because it is considered an accidental operational accident. In the face of crisis, PT. KAI implements the rebuild strategy through apologies, providing information regularly, conveying empathy, and active interaction on social media. From an ORM perspective, companies leverage social media to manage public perception, respond to criticism, and keep the flow of information under control.